Application of Improved Fuzzy-Set Pair Analysis in Mine Water Environmental Quality Evaluation - Longqing, Shi; Li, He; Peihe, Zhai (Global Journal of Earth Science and Engineering, 2021)
Mine water is an important water resource, mine water resource is of great significance to realize the sustainable development of economy and society, and the evaluation of water quality is an important link of mine water resource. This paper will be improved in Nemerow index method is applied to the fuzzy-set pair analysis method of composite algorithm, and the water quality evaluation of Kongzhuang Mine in Xuzhou is carried out. Finally, compared with the evaluation results of set pair analysis method and grey clustering method, it is shown that the evaluation results of this method are reasonable and scientific, which can provide reliable basis for the utilization of mine water resources.